INFLUENCE OF PROCESS PARAMETERS ON CELLULASE PRODUCTION BY Trichoderma viride (MTCC 800) EMPLOYING SOLID STATE FERMENTATION - P. R. KAKDE; S. C. AITHAL * (The Journal of Research ANGRAU, 2022)
In this study, the effect of physico-chemical parameters on the production of cellulase from Trichoderma viride (MTCC 800) were examined using five different agricultural residues namely banana peel, groundnut shell, corn cob, sugarcane bagasse, and pigeonpea stalk. The process parameters examined were pretreatment method, supplementation media, initial media pH, incubation period, temperature, and leaching agent. Among the parameters studied, maximum cellulase production was obtained on all the substrates treated with 1 N H2SO4 supplemented with Mandel’s medium of pH 5.5-6 after 6-8 days of incubation at 30-36°C and 0.05 M phosphate buffer (pH 7.0) as a leaching agent.